Patterns of plant diversity in the Hantam-Tanqua-Roggeveld subregion of the succulent Karoo, South Africa - Van Rooyen, M.W. (Margaretha W.), 1950- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.